2018
DOI: 10.3390/en12010033
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Reconstruction Approach to Elevator Energy Conservation Based on a DC Micro-Grid in High-Rise Buildings

Abstract: Elevators were reported to cause an important part of building energy consumption. In general, each elevator has two operation states: The load state and power regeneration state. During operation, it has the potential to save energy by using regeneration power efficiently. In existing research, a set of energy storage devices are installed for every elevator, which is highly costly. In this paper, an energy conservation approach for elevators based on a direct current (DC) micro-grid is proposed, which has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…Experimental and field data for high‐rise buildings revealed energy efficiencies up to 23.1% and 54.5%, respectively, favoring practical application of the strategy in near future. [ 33 ]…”
Section: Supercapacitors In Energy Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental and field data for high‐rise buildings revealed energy efficiencies up to 23.1% and 54.5%, respectively, favoring practical application of the strategy in near future. [ 33 ]…”
Section: Supercapacitors In Energy Managementmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] They can be utilized in a wide range of applications such as electric vehicles (EVs) and hybrid electric vehicles (HEVs), pulsing techniques, digital devices [18][19][20][21][22][23][24][25][26][27] as well as in other fields of energy and power quality management. [28][29][30][31][32][33][34][35][36][37] Meanwhile, management of material wastes generated from various sources including electrochemical devices has long been a matter of concern. A study by World Bank revealed that food and green wastes account for about 44% of the total waste generated in the world (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…However, the elevator traffic and characteristic parameters of the elevator speed profile were not considered. In [26], an energy-saving approach was proposed for a group of elevators based on a DC microgrid. An energy-efficient device based on supercapacitors was developed for the elevator group, and experimental tests showed that the energy savings ranged from 15.9 to 23.1% and 24.1 to 54.5% depending on the experiments conducted.…”
Section: Introductionmentioning
confidence: 99%
“…In elevator operation, regenerative braking energy is mainly dissipated on braking resistors [1], [2]. Therefore, how to reduce energy consumption in these vertical transportation systems has long been one of hot research issues to pay much attention from scientists, engineers.…”
Section: Introductionmentioning
confidence: 99%